Implementation of Leading Indicators on K3 Performance in Offshore Oil and Gas Drilling Jack-Up Rig XYZ - Juni Robinhot Tamba; Edi Setiawan (Journal of Social Research, 2025)
The offshore oil and gas drilling industry is a high-risk sector where effective Occupational Health and Safety (OHS) management is critical. This study examines the implementation of leading and lagging safety indicators and their impact on safety and drilling performance aboard Jack-Up Rig XYZ, operating under Saudi Aramco. Using a quantitative approach, the study analyzed 12 months of operational data through Pearson correlation and multiple linear regression. Findings revealed a significant negative correlation between leading indicators (e.g., Safe Observation Cards, audit compliance) and Non-Productive Time (NPT), with higher proactive safety measures corresponding to reduced downtime. However, lagging indicators (e.g., incident rates) showed no significant impact on drilling performance. The regression model explained 91.4% of NPT variation, underscoring the value of leading indicators in predictive safety management. Implications suggest that rig operators should prioritize leading indicators to enhance operational safety and efficiency, though technical drilling metrics like Rate of Penetration (ROP) remain influenced more by geological and engineering factors. This research provides empirical support for integrating proactive OHS measures into daily rig management practices.